2017
DOI: 10.3389/fnmol.2017.00244
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Triggers Expression of Immediate Early Genes and Differentially Affects the Expression of AMPA and NMDA Subunits in Dorsal and Ventral Hippocampus of Rats

Abstract: Previous studies in rats have demonstrated that chronic restraint stress triggers anhedonia, depressive-like behaviors, anxiety and a reduction in dendritic spine density in hippocampal neurons. In this study, we compared the effect of repeated stress on the expression of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) and N-methyl-D-aspartate (NMDA) receptor subunits in dorsal and ventral hippocampus (VH). Adult male Sprague-Dawley rats were randomly divided into control and stressed groups, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 77 publications
1
39
0
Order By: Relevance
“…It is worth noting that brain tissues were extracted from the entire hippocampus in this study. Considering that glutamate receptor subunits are differentially expressed and regulated in dorsal and ventral hippocampus (Pandis et al, 2006 ; Pacheco et al, 2017 ), future studies are needed to scrutinize MK-801-induced effects on glutamate receptor subunits in each subregion and to examine how these effects can be modulated by antipsychotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that brain tissues were extracted from the entire hippocampus in this study. Considering that glutamate receptor subunits are differentially expressed and regulated in dorsal and ventral hippocampus (Pandis et al, 2006 ; Pacheco et al, 2017 ), future studies are needed to scrutinize MK-801-induced effects on glutamate receptor subunits in each subregion and to examine how these effects can be modulated by antipsychotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…NMDA receptor subunits (NR1, NR2A, and NR2B) and AMPA receptor subunits (GluA1 and GluA2) are closely involved in brain function, and are also important targets of chronic stress ( Costa-Nunes et al, 2014 ; Pacheco et al, 2017 ; Shang et al, 2017 ; Arcego et al, 2018 ). The effects of chronic stress on NMDA and AMPA receptors vary based on the type of stress.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of chronic stress on NMDA and AMPA receptors vary based on the type of stress. For example, Pacheco et al (2017) found that restraint stress (2.5 h/day) for 14 days triggered an increase in NR1 protein level in the dorsal hippocampus. Arcego et al (2018) found that social isolation stress increased the expression of subunit NR2A of the NMDA receptor.…”
Section: Discussionmentioning
confidence: 99%
“…PPT in the hippocampus of female rats and mice (Li et al, 2004;Waters et al, 2009) and because it's reduced in the PFC of individuals with MDD (Feyissa et al, 2009) and with chronic stress exposure in rodents (Kallarackal et al, 2013;Kim and Leem, 2016;Pacheco et al, 2017). PSD-95 protein expression was quantified in hippocampus and frontal cortex samples using a PSD-95 kit from MSD (catalogue no.…”
Section: Psd-95 Quantification: Psd-95 Was Quantified Because Its Expmentioning
confidence: 99%
“…Estradiol and ERα or β agonist upregulate the expression of synaptic proteins in female rats (Waters et al, 2009), including the postsynaptic density protein 95 (PSD-95), a scaffolding protein which organizes synaptic elements that are important for synaptic function and plasticity (Kim and Sheng, 2004). Importantly, PSD-95 is reduced in the prefrontal cortex (PFC) of individuals with MDD (Feyissa et al, 2009) and in animal models of stress exposure (Kallarackal et al, 2013;Kim and Leem, 2016;Pacheco et al, 2017). Yet, whether and by what receptor mechanisms can 17β-estradiol influence the effects of stress on PSD-95 remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%